Hubungan Aktivitas Mengikuti Layanan Konseling Kelompok dengan Kepercayaan Diri Mahasiswa PIAUD STAI Auliurrasyidin Tembilahan - Suci Lia Sari; Rika Devianti (STAI Auliaurrasyidin Tembilahan, 2020)
The purpose of the research is to identify (1) the level of the STAI Auliaurrasyidin students’ activeness on group counselling, (2) the level of the STAI Auliaurrasyidin students’ confidence, and (3) whether there is a significant impact on the students’ activeness on group counselling to the STAI Auliaurrasyidin students’ confidence. This research took PIAUD students as subject, and those of who joined the counselling (29 students) were taken as object of the research. A Likert scale questionnaire was used to bring data together. Product moment was used to analyze correlation among data. Accordingly, they shown that (1) students’ activeness was at medium category (82.85%), (2) students’ confidence was at medium category (62.85%), and (3) correlation coefficient was at 0.671. This thus presented that there was a significant correlation between group counselling and STAI Auliaurrasyidin students’ confidence.